2015
DOI: 10.4067/s0717-95022015000400063
|View full text |Cite
|
Sign up to set email alerts
|

Equine Anatomedia: Development, Integration and Evaluation of an E-Learning Resource in Applied Veterinary Anatomy

Abstract: SUMMARY:In Egypt, there is a growing movement to encourage veterinary student-centered learning using the most up to date educational technologies. This paper focuses on a computer-facilitated learning program "Equine Anatomedia", which comprises now two modules (head and digit) fully integrated with the applied anatomy curriculum at Alexandria and Damanhour Universities. The educational design of this program allows students and clinicians to explore anatomical concepts, principles and procedure guidelines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Users can solve exercises and quizzes while exploring 2D images and 3D models interactively. Other interactive e-learning platforms exist, however, many are species specific ( El Sharaby et al, 2015 ; Raffan et al, 2017 ).…”
Section: Interactive Graphicsmentioning
confidence: 99%
“…Users can solve exercises and quizzes while exploring 2D images and 3D models interactively. Other interactive e-learning platforms exist, however, many are species specific ( El Sharaby et al, 2015 ; Raffan et al, 2017 ).…”
Section: Interactive Graphicsmentioning
confidence: 99%
“…Note that most of the platforms are nonweb-based (some of them are delivered in CD-ROM format), or they require the users to install one or more plug-ins to run the application in a web browser, such as the ones presented by Dale et al (2005), Ertmer and Nour (2007), and Pop et al (2013). Only 2 of them (Grizzle et al, 2008;El Sharaby et al, 2015) seem to work in a web browser without the need for any plug-ins, although this is not specified in the corresponding publications. Besides, none of them describes the possibility to run the application using a mobile device, such as a smartphone or a tablet.…”
Section: Comparison Of Ivet With the Selected Platformsmentioning
confidence: 99%
“…Different studies confirmed the need for a modernization process in veterinary education (Short, 2002;Simões, 2010;Ozkadif and Eken, 2012;Valliyate et al, 2012), as well as the benefits of e-learning environments (Bing et al, 2011;Jan et al, 2012;Dorosh et al, 2013). Nonetheless, few environments have been proposed in this field, and most of them only deal with single parts of the animal body or with a particular species of animals (Tawfiek, 2011;El Sharaby et al, 2015;Raffan et al, 2017). To overcome this limitation, the Interactive Veterinary Education Tool (IVET) is proposed, a new educational platform specifically designed to support teaching and learning in veterinary science with no restrictions on animal species.…”
Section: Introductionmentioning
confidence: 97%
“…Resources such as the use of live animals, cadavers, gross dissections, anatomic sections, and plastination enhance anatomic learning by researchers, students, and technicians [ 14 , 15 , 16 , 17 , 18 ]. In recent years, technological developments in the area of computer-assisted learning have improved anatomy teaching [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%